2015
DOI: 10.1016/j.physbeh.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha-tocopherol associated with lovastatin on brain tissue and memory function in SHRSPs

Abstract: Strokes are preceded by oxidative stress and inflammation, two processes linked to atherosclerosis and hypertension. Statins have been widely employed to control atherosclerosis; however, there could be neurological implications to its use—including cognitive impairment. Thus,we aimed to determine whether alpha-tocopherol is capable of reversing the neurological side effects of statins and enhancing its anti-inflammatory properties. To assess these effects, 15-week-old stroke-prone spontaneously hypertensive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(35 reference statements)
1
4
0
1
Order By: Relevance
“…The presented results revealed that the recognition index was significantly lower in the α-Tocopherol induced groups (STZ + α-Tocopherol 14) than in the icv-STZ group. Consistent with our data, Guimaraes et al (2015) showed that α-Tocopherol could modulate memory formation and preserve cognition in the Stork model ( Guimaraes et al, 2015 ). Sarmento-Silva et al (2014) conducted the antioxidant effects of α-Tocopherol in improving motor and cognitive deficits induced by chronic reserpine in rats.…”
Section: Discussionsupporting
confidence: 89%
“…The presented results revealed that the recognition index was significantly lower in the α-Tocopherol induced groups (STZ + α-Tocopherol 14) than in the icv-STZ group. Consistent with our data, Guimaraes et al (2015) showed that α-Tocopherol could modulate memory formation and preserve cognition in the Stork model ( Guimaraes et al, 2015 ). Sarmento-Silva et al (2014) conducted the antioxidant effects of α-Tocopherol in improving motor and cognitive deficits induced by chronic reserpine in rats.…”
Section: Discussionsupporting
confidence: 89%
“…Beside our results suggest that chronic Cbl administration, improved the memory function in the aged SH rats with a trend to reduce locomotor hyperactivity in a novel environment. Interestingly, several reports suggested that SH rats showed spatial memory deficits with hyperactivity behavior (Gr€ unblatt et al, 2015;Guimarães et al, 2015;Kaiser et al, 2014;Yin et al, 2014). Therefore, SH rats are used as an animal model of attention-deficit/hyperactivity disorder (AD/HD) and animal model of VD.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A is also important for maintaining immune function and plays an essential role in the development of T-helper and B cells [13]. The primary forms of vitamin A are retinol, retinoic acid, and retinal, whereas the form stored in the liver is retinyl palmitate [14].…”
Section: Introductionmentioning
confidence: 99%